Field emission cathode based on three-dimensional framework carbon and its operation under the driving of a triboelectric nanogenerator. (July 2018) - Chen, Jiangtao; Yang, Bingjun; Lim, Yu Dian; Su, Lijun; Yang, Juan; Guo, Ruisheng; Tay, Beng Kang; Yan, Xingbin
Abstract: The key factor in the functional performance of field emission devices (FEDs) is the selection of cold cathode materials. In this study, conductive, interconnected three-dimensional framework carbon (3DFC) with rich sharp edges acting as the emission sites is chosen as the cold cathode material. The distinguished field emission properties of 3DFC emitter yield low turn-on (2.6 V μm −1 ) and threshold (3.2 V μm −1 ) fields, with outstanding emission stability under conventional DC power supply. Apart from the excellent field emission properties, it is also demonstrated that the 3DFC cold cathode can be driven by triboelectric nanogenerator (TENG), a novel emerging energy-harvesting technology which harvests mechanical energy into electric energy. Assembling the TENG with 3DFC cold cathode, instantaneous, uniform emission behavior is obtained, as characterized by the field emission measurements and the luminance pattern of the 3DFC. In summary, this work presents novel 3DFC as a high performing cold cathode emitter driven by energy-harvesting TENG, where the obtained outcomes provide a strategy to further miniaturization of FEDs, promoting its applications in light weight, modern electronic devices. Graphical abstract: fx1 Highlights: A new type of cold cathode is made by using three-dimensional framework carbon. The emitter shows good field emission performance under conventional power supply. Triboelectric nanogenerator can drive field emission of the cold emitter.